Business Development Strategy Planning at PT Tunas Abadi Indoagro (Case Study at PT Tunas Abadi Indiagro) - Bagus Amerta (Universitas Ciputra Surabaya, 2022)
Business development in the agricultural sector is an effort to develop and increase agricultural products as an effort to meet the food needs of the community, the area of agricultural land is a potential natural resource owned by Indonesia so that a good agricultural sector development will increase economic growth in Indonesia. PT Tunas Abadi Indoagro serves distribution of fertilizers and pesticides in East Java and Bali with different needs according to the commodities grown in the background. the last year due to home-made products and also the long dry season caused the company's sales turnover to decrease compared to before. The method used in this study was a qualitative method, data collection was carried out by means of interviews and resource persons consisted of the internal parties of Pt Tunas Abadi Indoagro consist of the owner to the staff. The variables used in this study are PEST (political, economic, social and technology) as well as five porter analysis, after that the result are being analyzed using SWOT method (strength, weakness, opportunity and threat) analysis. that leads to the conclusion that there are several things that need to be considered in business development planning such as the buyer making price comparisons, many new competitors, high competition Products have the same function, on the other hand the company still has strengths such as being able to choose fertilizer and pesticide products Experienced in business agriculture, supplier trust the number of products sold is a lot that the company PT Tunas Abadi Indoagro must maintain.